Integrated environmental management : where is South Africa headed given recent developments relating to NEMA and the Infrastructure Development Act? - Day, Kirsten Dea (Institute of Marine and Environmental Law, 2015)
Integrated Environmental Management (IEM) was formulated during the 1980s by the Council for the Environment in response to a dual need in South Africa to effectively manage the country's natural resource base whilst stimulating economic growth and development. The IEM principles were translated into the National Environmental Management Act (NEMA) in 1998, and IEM also became the title of Chapter 5, the purpose of which is to promote the application of appropriate environmental management tools to ensure the integrated environmental management of activities. Over the years a single tool, namely, environmental impact assessment (EIA) has come dominate the environmental management regime in South Africa, and many of the innovative attributes of IEM have been diluted with a more conventional and conservative approach to impact assessment. EIA has consequently been blamed for causing delays and undermining the national government's infrastructural development ambitions for the country. In 2014 the Department of Economic Development introduced the Infrastructure Development Act (IDA) which is aimed at prioritising public infrastructure projects seen to be of significant economic or social importance. This dissertation focuses on those factors that compel a comparison between NEMA and the IDA, not least of which is the provision for lists of projects and activities subject to legislated requirements. Whereas NEMA aims to ensure that such activities are planned, assessed and monitored in accordance with principles of sustainable development, the IDA seeks to expedite development in the face of lack of employment opportunities, an energy crises and falling GDP growth rates. The outcome of a comparison between NEMA and the IDA suggests that overly complex and arduous environmental procedures and legislative requirements have precipitated an extreme response. However, the steam-roller type approach advocated by the IDA is likely to create more problems than solutions as it ignores government's concurrent commitments to co-operative governance and sustainability. The original principles and procedures of IEM provide a potential alternative to ensuring a balance between environmental protection and economic growth.